How the Pension System Responds to Pandemic Shocks: A Case Study of Georgia - Maka Ghaniashvili (European Scientific Journal, ESJ, 2021)
The paper focuses on the impact of the pandemic crisis on pension system in Georgia and analyzes the pros and cons of the ongoing pension reforms in the country. Decreased birth rates and increased life expectancy over the next decades will significantly change the picture of the age distribution of the population in many countries. As life expectancy increases and the birth rate decreases, more people retire than are added to the workforce. A change in the demographic picture necessitates fundamental pension reform. At the same time, the world is facing a crisis caused by the COVID-19 pandemic. The future is uncertain, both medically and financially. Despite optimistic forecasts, the second wave of the COVID-19 pandemic has begun in many countries which further increases the degree of uncertainty. Funded pension schemes suffer from the crisis because lower returns diminish their asset values, while low yields on public debt instruments increase the present value of their liabilities. This can generate both explicit fiscal risks— in the case of government guarantees—and implicit fiscal risks through lower private pension benefits or financial strain on the sponsoring employers. Our research is focused on the pension system and its development problems in Georgia, taking into account that since 2019, 1st January, the existing financial, demographic and economic challenges have determined the establishment of a new pension system. Main sources for the research are data gathered from the international organizations and local governmental and statistical data softwares. Our research results show that the pension reform launched in 2019 in Georgia is a significant step forward in reducing social imbalances and fiscal pressures in the medium / long term. However, for further development, it is important to systematically assess the effectiveness of pension policies, taking into account factors such as changes in demographic structure, expected fiscal spending, the inequality gap and the crisis caused by the COVID-19 pandemic.